Chaotic signal generation and coding using a nonlinear micro ring resonator - Mitatha, S.; Dejhan, K.; Yupapin, P. P.; Pornsuwancharoen, N. (My University, 2010)
We propose a new digital encoding method using light pulses tracing in a micro ring resonator, where the randomly digital codes can be performed. The chaotic signals can be generated and formed by the logical pulses "1" or "0" by using the signal quantizing method, which can be randomly coded by controlling the specific optical input coupling powers, i.e. coupling coefficient (κ) and ring radii. Simulation results when the ring radius used is 10.0 μm, and the other selected parameters are close to the practical device values that are presented and discussed. The random codes can be generated by the random control of coupling powers, which can be transmitted and retrieved via the design filters by the specific clients. For instance, the controlled input power used is between 2.0 and 3.5 mW, whereas the quantizing threshold powers and the traveling roundtrips are 0.3-0.4 mW and 8000-10,000, respectively. In application, the required information can be generated, and the information can be securely transmitted in the public link. © 2008 Elsevier GmbH. All rights reserved.
Keywords: Chaotic communication; Chaotic encoding; Nonlinear optical communication